Relationships between Ambient Ozone Concentration Changes in Southwestern Taiwan and Invasion Tracks of Tropical Typhoons - Chung-Hsuang Hung; Kuo-Cheng Lo (Advances in Meteorology)
This study aimed to use a newly developed weather and air quality model, WRF-Chem, to simulate and analyze formation of high-concentrated ozone (O3) in the ambient air of southwestern Taiwan before the invasion of tropical typhoons. Two typical typhoons, Nanmadol and Usagi that occurred in 2011 and 2013, respectively, were simulated in this study. The O3 concentration variation patterns in the ambient air of both offshore and inland parts of southwestern Taiwan were collected and analyzed. The results indicated that the high O3 concentration observed in southwestern Taiwan before typhoon arrived was mainly caused by the western Pacific subtropical high (WPSH) shrouding it. On the other hand, the latter increase in ambient O3 concentration about 1 to 2 days before issuing sea warning was mainly due to both contributions of weakening WPSH and intensifying leeward side effects. For both cases, atmospheric subsidence occurred to result in low ambient air quality. The invasion of typhoons made ambient O3 concentration enhanced up to 2-3-fold compared to its normal concentration in summer. Based on the simulated O3 concentration variation results in this study, it is demonstrated that the space-fading patterns of O3 before typhoon arrives also can be used as references for predicting typhoon moving tracks 1.0 to 2.0 days before landfall of typhoons.